Memulai Usaha dari Rumah - Merliyana; Saefurahman, Asep; Hendrawati; Chandra, Rama; Burda, Agustian; Mais, Rimi Gusliana (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This community service activity aims to enhance the entrepreneurial knowledge and skills of housewives in RT 03 RW 010, Puri Bukit Depok housing area, in starting home-based businesses. Using an educational and participatory approach, the program focuses on empowering household-based economic activities by leveraging local potential and simple technology. The program was carried out through presentations, group discussions, and hands-on practices related to basic entrepreneurship, identifying business opportunities, and product marketing strategies using social media. The results show high enthusiasm among participants, improved understanding of entrepreneurship, and initial planning of home businesses aligned with their individual skills and conditions. This activity is expected to serve as a sustainable starting point in developing micro-entrepreneurs among housewives.